Venous Thromboembolic Complications in Pediatric Gastrointestinal Diseases: Inflammatory Bowel Disease and Intestinal Failure - Klomberg, Renz C. W.; Vlug, Lotte E.; de Koning, Barbara A. E.; de Ridder, Lissy (Frontiers in Pediatrics, 2022)
In children with gastrointestinal disorders such as inflammatory bowel disease (IBD) and intestinal failure (IF), the risk of venous thromboembolism (VTE) is increased. VTE may lead to pulmonary embolism, sepsis and central line infection, stroke and post-thrombotic syndrome. The purpose of this review is to summarize current knowledge and recent advances around VTE management in pediatric gastroenterology with a focus on IBD and IF. The VTE incidence in children with IBD is reported to be around 4–30 per 10,000 patient-years, with higher incidences for hospitalized children. While in general, IF is less common than IBD, the VTE incidence in children with IF is around 750 per 10,000 patient-years. The most common risk factors for development of VTE involve deviations leading to Virchow's triad (endothelial damage, stasis, and hypercoagulability) and include active inflammation, particularly with colonic involvement, presence of a central venous catheter, underlying thrombophilia, reduced mobility, surgery, and hospitalization. Classes of anticoagulants used for treatment of VTE are low molecular weight heparins and vitamin K antagonists. However, the use of direct oral anticoagulants for treatment or prevention of VTE has not been studied in this pediatric population yet. Pediatric gastroenterologists apply different VTE prevention and treatment strategies due to lack of literature and lack of consensus. We discuss the role of primary and secondary prophylactic use of anticoagulants, and provide tools and recommendations for screening, prevention and management for the specific pediatric populations.